Kajian Pengendalian Perubahan Penggunaan Lahan Pertanian Di Kecamatan Moncongloe Kabupaten Maros - Aprilian Kembong, Piskah; Salim, Agus; Arief, Rimba (Fakultas Teknik Universitas Bosowa, 2023)
Land has an important role and is the main factor for realizing physical development and will experience changes from time to time. This study identified the levels and factors of changes in the function of agricultural land and identified directions for controlling changes in agricultural land use into built-up areas in Moncongloe District, Maros Regency. Linear Regression analysis is used to determine the variables that influence changes in land use. The conclusion from this study is that the factors causing changes in the use of agricultural land, namely, the good accessibility factor, are a high attraction for urbanization actors to live, so that population growth continues to increase accompanied by housing needs which require a lot of agricultural land to be converted to meet community needs. . Thus, the control direction taken is a strategy to control land use change based on the Spatial Plan and solutions to the factors causing land use change to prevent land use change that is not in accordance with the Spatial Plan in Moncongloe District, Maros Regency.